Peptide and glycopeptide dendrimers and analogous dendrimeric structures and their biomedical applications - Šebestík, Jaroslav; Niederhafner, Petr; Ježek, Jan (Amino acids, 2011)
The size of information that can be stored in nucleic acids, proteins, and carbohydrates was calculated. The number of hexamers for peptides is 64,000,000 (20(6)) and seems to be impressive in comparison with 4,096 (4(6)) hexanucleotides, but the number of isomers of hexasaccharides is 1.44 × 10(15). Carbohydrates are therefore the best high-density coding system. This language has been named glycocode resp. sugar code. In comparison with peptide dendrimers, the amount of information carried by glycopeptide dendrimers or glycodendrimers is therefore much higher. This is reflected by the variability of structures and functions (activities). This review is about the broad area of peptide and glycopeptide dendrimers. The dendrimeric state and physicochemical properties and general consequences are described, together with a cluster effect. The impact of cluster effect to biological, chemical, and physical properties is discussed. Synthesis of dendrimers by convergent and divergent approaches, "Lego" chemistry, ligation strategies, and click chemistry is given with many examples. Purification and characterization of dendrimers by chromatographic methods, electromigration methods, and mass spectrometry are briefly mentioned. Different types of dendrimers with cyclic core, i.e. RAFTs, TASPs and analogous cyclic structures, carbopeptides, carboproteins, octopus glycosides, inositol-based dendrimers, cyclodextrins, calix[4]arenes, resorcarenes, cavitands, and porphyrins are given. Dendrimers can be used for creation of libraries, catalysts, and solubilizing agents. Biocompatibility and toxicity of dendrimers is discussed, as well as their applications in nanoscience, nanotechnology, drug delivery, and gene delivery. Carbohydrate interactions of glycopeptide dendrimers (bacteria, viruses, and cancer) are described. Examples of dendrimers as anti-prion agents are given. Dendrimers represent a fast developing area which partly overlaps with nanoparticles and nanotechnologies.
Keywords: Gene Targeting; Glycopeptides; dendrimery; Animals; farmakoterapie; genový targeting; lidé; nanotechnologie; Dendrimers; glykopeptidy; Drug Therapy; Humans; zvířata; Peptides; peptidy; Drug Delivery Systems; lékové transportní systémy; Nanotechnology